Evaluation of Selective Broadcast Algorithms for Safety Applications in Vehicular Ad Hoc Networks - Bür, Kaan; Kihl, Maria (International journal of vehicular technology, 2011)
Just as wireless communications develop further to achieve higher performance, new application areas emerge to challenge the limits. Vehicular ad hoc networks are one of these areas, and emergency situation warning is one of their most popular applications since traffic safety is a concern for everyone. Due to the life-critical nature of emergency applications, however, it is extremely important to ensure the solutions proposed meet the standards required, such as reliable and timely delivery of the safety warning in a situation like car collision avoidance. In order to put the candidate solutions to the test and evaluate their feasibility, we adopt the approach of computer simulation. We implement four different selective broadcast algorithms used for information dissemination in vehicular ad hoc networks, and compare their performance under identical realistic simulation conditions. Our goal is to provide an evaluation focussing on the performance with respect to safety, rather than to network aspects like throughput, loss, and delay. We define four new performance criteria to address the effectiveness, efficiency, timeliness, and overhead of the broadcast algorithms in safety warning delivery. The results we obtain using these criteria help us to understand better the design requirements of a high-performance selective broadcast algorithm.